Printed from https://www.webqc.org

Chemical Equations Balanced on 02/22/25

 Equations balanced on the previous day Equations balanced on the next day
Balance the equation of any chemical reaction
Cu + (AgNO3) = Ag + Cu(NO3)2 =>
Cu + 2(AgNO3) = 2 Ag + Cu(NO3)2

Al + H2SO4 = Al2(SO4)3 + H2 =>
2 Al + 3 H2SO4 = Al2(SO4)3 + 3 H2

H2O2 + (CH3)3N = H2O + (CH3)3NO =>
H2O2 + (CH3)3N = H2O + (CH3)3NO

C = C2 =>
2 C = C2

Cu + HNO3 = Cu(NO3)2 + NO2 + H2O =>
Cu + 4 HNO3 = Cu(NO3)2 + 2 NO2 + 2 H2O

Na(s) + H2(g) + C(s) + O2(g) = NaHCO3 =>
2 Na(s) + H2(g) + 2 C(s) + 3 O2(g) = 2 NaHCO3

Al + H2SO4 = Al2SO4 + H =>
2 Al + H2SO4 = Al2SO4 + 2 H

Al + H3PO4 = AlPO4 + H2 =>
2 Al + 2 H3PO4 = 2 AlPO4 + 3 H2

C4H10 + O2 = CO2 + H2O =>
2 C4H10 + 13 O2 = 8 CO2 + 10 H2O

Mg(HSO4)2 = MgSO4 + H2SO4 =>
Mg(HSO4)2 = MgSO4 + H2SO4

CH3CHO + Cu(OH)2 + NaOH = CH3COONa + Cu2O + H2O =>
CH3CHO + 2 Cu(OH)2 + NaOH = CH3COONa + Cu2O + 3 H2O

C17H35COOH + O2 = CO2 + H2O =>
C17H35COOH + 26 O2 = 18 CO2 + 18 H2O

Al + HBr = AlBr3 + H =>
Al + 3 HBr = AlBr3 + 3 H

Al + HCl = AlCl + H2 =>
2 Al + 2 HCl = 2 AlCl + H2

H3PO2 + HNO3 = H3PO4 + NO2 + H2O =>
H3PO2 + 4 HNO3 = H3PO4 + 4 NO2 + 2 H2O

CuSO4() + NaOH() = Cu(OH)2() + Na2SO4() =>
CuSO4() + 2 NaOH() = Cu(OH)2() + Na2SO4()

Fe2O3 + CH4 = CO2 + Fe3O4 + H2 =>
6 Fe2O3 + CH4 = CO2 + 4 Fe3O4 + 2 H2

CaSO3 + H3BO3 = Ca3(BO3)2 + SO2 + H2O =>
3 CaSO3 + 2 H3BO3 = Ca3(BO3)2 + 3 SO2 + 3 H2O

AgNO3 + CsCl = AgCl + CsNO3 =>
AgNO3 + CsCl = AgCl + CsNO3

Al(s) + O2 = Al2O3(aq) =>
4 Al(s) + 3 O2 = 2 Al2O3(aq)

KI(s) + MnO2(aq) + H2SO4(aq) = I2(g) + MnSO4(aq) + KHSO4(aq) + H2O(l) =>
2 KI(s) + MnO2(aq) + 3 H2SO4(aq) = I2(g) + MnSO4(aq) + 2 KHSO4(aq) + 2 H2O(l)

[NiCl2(PPh3)2] + CH2Cl2 = [NiCl2(PPh3)2]*2CH2Cl2 =>
[NiCl2(PPh3)2] + 2 CH2Cl2 = [NiCl2(PPh3)2]*2CH2Cl2

C6H5ONa + O2 = Na2CO3 + CO2 + H2O =>
2 C6H5ONa + 14 O2 = Na2CO3 + 11 CO2 + 5 H2O

K2SO4 + TiOSO4 + H2O2 + H2O = K2[TiO2(SO4)2]*3H2O =>
K2SO4 + TiOSO4 + H2O2 + 2 H2O = K2[TiO2(SO4)2]*3H2O

Al + HCl = AlCl3 + H2 =>
2 Al + 6 HCl = 2 AlCl3 + 3 H2

Mn(NO3)2 + Na3(BiO4) + HNO3 = Bi(NO3)2 + HMnO4 + NaNO3 + H2O =>
3 Mn(NO3)2 + 5 Na3(BiO4) + 19 HNO3 = 5 Bi(NO3)2 + 3 HMnO4 + 15 NaNO3 + 8 H2O

AgCl + HPO3 = AgPO3 + HCl =>
AgCl + HPO3 = AgPO3 + HCl

K2O + H2O = KOH = K2O + H2O + KOH =>
K2O + H2O = 2 KOH

La100(N100O300)300*600H200O100 + Sr100(N100O300)200 + Cr100(N100O300)300*900H200O100 + Mn100(N100O300)200*200H200O100 + C600H800O700 = La75Sr25Cr50Mn50O300 + H200O100 + C100O200 + N100O200 =>
3 La100(N100O300)300*600H200O100 + Sr100(N100O300)200 + 2 Cr100(N100O300)300*900H200O100 + 2 Mn100(N100O300)200*200H200O100 + 232 C600H800O700 = 4 La75Sr25Cr50Mn50O300 + 4928 H200O100 + 1392 C100O200 + 2100 N100O200

HBr(aq) + Pb(NO3)2(aq) = PbBr2(s) + HNO3(aq) =>
2 HBr(aq) + Pb(NO3)2(aq) = PbBr2(s) + 2 HNO3(aq)

Rb(s) + RbNO3(aq) = Rb2O(s) + N2(g) =>
10 Rb(s) + 2 RbNO3(aq) = 6 Rb2O(s) + N2(g)

Al + HCl = H2 + AlCl3 =>
2 Al + 6 HCl = 3 H2 + 2 AlCl3

C2(d) + O2 = CO2 =>
C2(d) + 2 O2 = 2 CO2

(N2Cl4)3 + (CH4)3 = (N2)3 + (H2)6 + (CCl4)3 =>
(N2Cl4)3 + (CH4)3 = (N2)3 + (H2)6 + (CCl4)3

Al + NH4ClO4 = Al2O3 + AlCl3 + NO + H2O =>
3 Al + 3 NH4ClO4 = Al2O3 + AlCl3 + 3 NO + 6 H2O

FeO3 + H2SO4 = H2O + FeSO6 =>
FeO3 + H2SO4 = H2O + FeSO6

CH3OH + K = CH3OK + H2 =>
2 CH3OH + 2 K = 2 CH3OK + H2

C9OHS2I2 + Br2 = C9OHS2Br2 + I2 =>
C9OHS2I2 + Br2 = C9OHS2Br2 + I2

Al + NaOH + H2O = NaAlO2 + H =>
Al + NaOH + H2O = NaAlO2 + 3 H

KCIO3 = KCI + O3 =>
KCIO3 = KCI + O3

O2 + Cl2O2 = Cl2O5 =>
3 O2 + 2 Cl2O2 = 2 Cl2O5

Cu(NO3)2 + H2SO4 = CuSO4 + HNO3 =>
Cu(NO3)2 + H2SO4 = CuSO4 + 2 HNO3

Al + O = Al2O3 =>
2 Al + 3 O = Al2O3

K2CrO4(aq) + (NH4)2SO4(aq) = NH3(aq) + K2Cr2O7(aq) + K2SO4(aq) + H2O(l) =>
2 K2CrO4(aq) + (NH4)2SO4(aq) = 2 NH3(aq) + K2Cr2O7(aq) + K2SO4(aq) + H2O(l)

CH4 + O2 = CO2 + H2O =>
CH4 + 2 O2 = CO2 + 2 H2O

Al + O2 = Al2O3 =>
4 Al + 3 O2 = 2 Al2O3

Al + Pb(NO3)2 = Al(NO3)3 + Pb =>
2 Al + 3 Pb(NO3)2 = 2 Al(NO3)3 + 3 Pb

Na2[Sn(OH)4] + Bi2(SO4)3 + NaOH = Na2[Sn(OH)6] + Bi + Na2SO4 =>
3 Na2[Sn(OH)4] + Bi2(SO4)3 + 6 NaOH = 3 Na2[Sn(OH)6] + 2 Bi + 3 Na2SO4

C3H6 + HBr = C3H5Br + H2 =>
C3H6 + HBr = C3H5Br + H2

Mg + K2CO3 = MgCO3 + K =>
Mg + K2CO3 = MgCO3 + 2 K

1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78
Balance the equation of any chemical reaction
 Equations balanced on the previous day Equations balanced on the next day
Equations balanced on 02/15/25
Equations balanced on 01/23/25
Equations balanced on 02/22/24
Please let us know how we can improve this web app.
Menu Balance Molar mass Gas laws Units Chemistry tools Periodic table Chemical forum Symmetry Constants Contribute Contact us
How to cite?